Membrane Protein Sorting: Proteoliposome Engineering with Cell‐Free Membrane Protein Synthesis: Control of Membrane Protein Sorting into Liposomes by Chaperoning Systems (Adv. Sci. 10/2018). Issue 10 (17th October 2018) - Ando, Mitsuru; Schikula, Shun; Sasaki, Yoshihiro; Akiyoshi, Kazunari
Abstract : Cell‐free membrane protein (MP) synthesis in the presence of liposomes is a spotlighting technique to prepare MP‐reconstituted liposomes. In article number1800524, Kazunari Akiyoshi and co‐workers develop an artificial MP sorting system based on polyhistidine/nickel‐chelate affinity. This system enables efficient reconstitution of MPs into the liposomal membrane to be achieved, and supplementations of natural molecular chaperone can control the orientation of MPs.